Peran Polisi Daerah (Polda) Riau Dalam Upaya Pemberantasan Peredaran Buku Pemilik Kendaraan Bermotor (BPKB) Palsu - Kris Ridha Wahyuni; Nora Eka Putri (Jurusan Ilmu Administrasi Negara, 2023)
This study intends to determine the role of Polda Riau in efforts to eradicate the circulation of fake BPKB. This research was conducted using a qualitative approach with descriptive methods, in determining researcher informants using purposive sampling methods and techniques. Data collection techniques are carried out by interviews, observation, and documentation. In testing the validity of the data, researchers used method triangulation techniques. As for data analysis techniques using data reduction, data presentation, and conclusions. The results showed that theRiau Regional Police in an effort to eradicate the circulation of fake BPKB by means of (a) upay a preemptive by conducting socialization and education to the public about the dangers of circulating fake BPKB and the importance of checking the validity of vehicle documents before making motor vehicle buying and selling transactions. (b) preventive efforts have conducted surveillance of workshops and car dealers suspected of being involved in the circulation of fake BPKB. (c) repressive efforts have carried out investigations and investigations against the perpetrators of making fake BPKB such as by checking the same vehicle, and when checking through the database there are irregularities with the frame number, engine and type. If anyone violates, the Riau Regional Police provides strict sanctions for the perpetrators of the circulation of fake BPKB. Furthermore, f the inhibiting actors for the Riau Regional Police in carrying out efforts to eradicate the circulation of fake BPKB, namely (1) the lack of capabilities and resources owned by the Riau Regional Police; (2) lack of public awareness about the importance of knowledge related to the circulation of fake BPKB.